(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Background: the most common side effects include whiplash and spinal cord injuries which can result in severe physical and psychological effects that can change the patient’s quality of life. These conditions lead to chronic pain, disability and mental health problems, which require integrated care paradigms in order to enhance the quality of life and functioning of patients. Objectives: The purpose of this research is to determine the social and psychological status of the whiplash and spinal cord injury patients concerning their mental health, social inclusion, and quality of life. Study design: A cross-sectional study. Place and duration of study: Department Of Psychiatry Qazi Hussain Ahmed Medical Complex Nowshera from 05-July 2020 to 05-Dec 2020 Methods: A cross-sectional study was also conducted with 100 patients with whiplash and spinal cord injury from 05-July 2020 to 05-Dec 2020. Participants completed standardized questionnaires and interviews about their mental health status, social contacts, and quality of life. Results: This research identified that 60% of patients had moderate to severe depression and anxiety symptoms and 35% met the criteria for PTSD. Over half of the participants claimed they experienced social isolation, while many of them noted that their family relationships were strained and getting a job was challenging. These findings suggest the need to assist these students appropriately as they may require support. Conclusion: Whiplash and spinal cord injuries present severe social and psychological complications for the patients. Hence, it is vital to ensure that they undergo proper rehabilitation that entails; psychological and social support and vocational training in order to lead a better life.